2011
DOI: 10.5455/jmood.20111217095840
|View full text |Cite
|
Sign up to set email alerts
|

Psychopharmacological aspects of catha edulis (khat) and consequences of long term use: a review

Abstract: Bağıntı beyanı: N.T.W.: Yazarlar bu makale ile ilgili olarak herhangi bir çıkar çatışması bildirmemişlerdir.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 33 publications
2
10
1
Order By: Relevance
“…The prevalence of cognitive impairment among HIV-positive patients reported in the present study is very high compared to the report of multicenter international studies that revealed neuropsychological deficit among HIV-positive patients as 13% in Brazil and 18.4% in Thailand [ 5 ]. The prevalence of cognitive impairment reported in this study is also higher than the findings of other studies conducted in Malawi (14%) and Kenya (15.3%) [ 15 , 16 ] which showed that cognitive impairment occurred in 14% and 15.3% of the study populations, respectively. Different viral clades and screening tools used may account for the variation in the magnitude of neurocognitive impairment as certain clades may be more or less neuropathogenic.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…The prevalence of cognitive impairment among HIV-positive patients reported in the present study is very high compared to the report of multicenter international studies that revealed neuropsychological deficit among HIV-positive patients as 13% in Brazil and 18.4% in Thailand [ 5 ]. The prevalence of cognitive impairment reported in this study is also higher than the findings of other studies conducted in Malawi (14%) and Kenya (15.3%) [ 15 , 16 ] which showed that cognitive impairment occurred in 14% and 15.3% of the study populations, respectively. Different viral clades and screening tools used may account for the variation in the magnitude of neurocognitive impairment as certain clades may be more or less neuropathogenic.…”
Section: Discussioncontrasting
confidence: 81%
“…There is evidence that cognitive functioning in HIV is associated with disease severity (CD4 T-cell count level less than 200 cell/ μ l and plasma HIV-1 RNA load), advanced age, level of education, income level, social support, medical comorbidities, and HIV medication adherence [ 9 16 ]. Previous study showed that khat chewing declines memory and learning, resulting in cognitive impairment [ 16 , 17 ]. Moreover, age-related dementia usually happens at the age of 65 years and above [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the results of this study disclosed that any of the substances used were not associated with cognitive impairment. However, an experimental and cross-sectional study on human showed that khat chewing and alcohol drinking were associated with memory deficits and impair cognitive flexibility (Kimani and Nyongesa, 2008;Wabel, 2011;Colzato et al, 2011;Hoffman and al' Absi, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It becomes the most exported item next to coffee and oil seeds, and generates 10% of Ethiopia's export income ( Andualem, 2002 ; Bongard et al, 2011 ; Ezekiel. 2005 ; Wabel, 2011 ). Besides financial benefits, the plant also serves for fuelwood, construction and farming tools ( Gesess, 2013 ).…”
Section: Introductionmentioning
confidence: 99%